Vulnerabilidade socioambiental à inundação na área urbana de londrina – PR - Mirian Vizintim Fernandes Barros; Crislaine Mendes; Paulo Henrique Marques de Castro (Confins)
The use of indexes to characterize multiples socioeconomic and environmental parameters has been regularly used nowadays. Among these, the indexes for calculate the environmental vulnerability. The concept of vulnerability and the factors that compose it are not yet fully explored, although it constitutes an essential parameter to estimate the risk.The vulnerability relates to the presence of risk and the ability of people to mitigate the damage, which differs and make them more or less vulnerable taking into account the risk and their condition of confront it. This research presents a methodology to evaluate the social, infrastructural and environmental vulnerability to the risk of flooding in the urban area of Londrina (PR).The methodology for to calculate the vulnerability was adapted from Mendes (2013), using data from IBGE Census (2010) and the census tract as unit of analysis, because this is the smallest territorial unit with identifiable boundaries and appropriate size for research in population.For to calculate the Social Vulnerability and Infrastructure Index, 36 variables were selected, reclassified, resulting in 13 synthetic variables, distributed among six thematic indicators (education, income and age structure, sewage, rainwater drainage, housing conditions). The value of the indexes was the result of the sum between the synthetic variables. Thus, for each census tract, six specific indicators were generated and after staggered.The Environmental Vulnerability Index was calculated from the variables: slope, soil and riparian zone, fixed at 30 meters required by law. The mapping of each of these variables was extrapolated to the census tract, making possible the intersections. The overlay with the land use database gave the Potential Fragility Index. The Social Vulnerability, Infrastructure and Potential Fragility Indexes resulted in Socio-environmental Vulnerability Index.Using GIS tools by ArcGIS 9.3, multi-thematic maps were developed to understand the organization of the space and their vulnerabilities, which highlight the differences between the census tract in access to public services and urban infrastructure.